Role of Caveolin-1 in Sepsis – A Mini-Review - Lannes-Costa, Pamella Silva; Pimentel, Bruna Alves da Silva; Nagao, Prescilla Emy (Frontiers in Immunology, 2022)
Sepsis is a generalized disease characterized by an extreme response to a severe infection. Moreover, challenges remain in the diagnosis, treatment and management of septic patients. In this mini-review we demonstrate developments on cellular pathogenesis and the role of Caveolin-1 (Cav-1) in sepsis. Studies have shown that Cav-1 has a significant role in sepsis through the regulation of membrane traffic and intracellular signaling pathways. In addition, activation of apoptosis/autophagy is considered relevant for the progression and development of sepsis. However, how Cav-1 is involved in sepsis remains unclear, and the precise mechanisms need to be further investigated. Finally, the role of Cav-1 in altering cell permeability during inflammation, in sepsis caused by microorganisms, apoptosis/autophagy activation and new therapies under study are discussed in this mini-review.